Families & family therapy - Minuchin, Salvador (Harvard University Press, 1974)
No other book in the field so fully combines vivid clinical examples, specific details of technique, and mature perspectives on both effectively functioning families and those seeking therapy. The views and strategies of a master clinician are presented here in such clear and precise form that readers can proceed directly from the book with comparisons and modifications to suit their own styles and working situations. Salvador Minuchin presents six chapter-length transcripts of actual family sessions--two devoted to ordinary families who are meeting their problems with relative success; four concerned with families seeking help. Accompanying each transcript is the author's running interpretation of what is taking place, laying particular stress on the therapist's tactics and maneuvers. These lively sessions are interpreted in a brilliant theoretical analysis of why families develop problems and what it takes to set them right. The author constructs a model of an effectively functioning family and defines the boundaries around its different subsystems, whether parental, spouse, or sibling. He discusses ways in which families adapt to stress from within and without, as they seek to survive and grow. Dr. Minuchin describes methods of diagnosing or "mapping" problems of the troubled family and determining appropriate therapeutic goals and strategies. Different situations, such as the extended family, the family with a parental child, and the family in transition through death or divorce, are examined. Finally, the author explores the dynamics of change, examining the variety of restructuring operations that can be employed to challenge a family and to change its basic patterns.